Cycling in Japan and Great Britain: A Preliminary Discussion - Katia Andrade; Seiichi Kagaya (European Regional Science Association (ERSA), 2011)
Around the world, cycling has mostly been used for two main purposes. Some societies view and utilize the bicycle as an integral part of the transportation system. Even if not used as the main transportation mode, it can still be used efficiently as a complementary transportation mode to public transit modes. The Netherlands and Denmark are examples of European countries where cycling accounts for high daily shares. Among Asian countries, Japan and China present significant cycling rates. However, as the contemporary societies grow more auto-dependent, cycling has been merely seen as a means of recreation and rarely used for daily travel in many other countries. Examples are the United States, Australia and Great Britain where nationwide statistics suggest insignificant bicycle shares. As part of a larger research project, this paper presents a preliminary discussion on the use of bicycle in two countries with significantly different cycling characteristics, Great Britain and Japan. In most British cities, cycling is not an integral part of the transportation system, despite considerable efforts from government. Conversely, cycling is a widely accepted transportation mode throughout Japan, even though Japanese cities do not yet present extensive cycling networks. Traditionally, Japanese urban plans are limited to two main actions with regards to cycling; either implementing bicycle parking facilities around railway/subway stations, or establishing bicycle zones within road intersections. The main objective of this paper is to present an overview of each country's cycling system, with a focus on travel patterns and bicycle facilities. Initially, benefits from cycling are pointed out. Cycling trends are then compered, whilst bicycle infrastructure and service are summarized. The paper concludes by comparing transport policies and strategies towards cycling in these countries and discussing the relative merits of each approach.
Keywords: 330